The evolution and spatial diffusion of informal sector activity in Nigeria: A case study of informal tailoring industry in the Oyo State metropolitan areas. - Onyewuenyi, Remy N. (University of Ottawa (Canada), 1991)
One of the oldest traditional crafts that provided employment for a significant proportion of the Nigerian population and practised specially by the Oyo Yoruba, is dressmaking by hand. The introduction of colonial rule and sewing machine in the region in early nineteenth century, not only revolutionised the art of dressmaking, but it also created a new and non-traditional craft: tailoring--the art of making clothes with the aid of a sewing machine. Over the years, dressmaking by hand has given way to tailoring, and tailoring has gradually become a dominant industry in the field of informal sector activities in Oyo State. The objectives of the study are (1) to describe the evolution and spatial diffusion of informal tailoring industry in the Oyo State metropolitan system, (2) to measure and explain the pattern of spatial variations of the diffusion, and (3) to explain the role of colonial and post colonial systems in the development and spatial diffusion of the industry in the state. It is hoped that from the evidence presented in the study, we can speculate on what spatial and historical structures that promote or hinder the development of informal tailoring activity, at least in the Nigerian metropolitan areas. The study area is Yorubaland, where the bulk of the population is Yoruba. The observation units at the inter urban level are sixteen selected centres, consisting of eleven divisional and five non-divisional headquarter towns. The intra urban observation units are the forty-five administrative wards and sub-wards of the Ibadan metropolitan area. In order to reconstruct and explain the historical and geographical evolution of the informal tailoring industry in colonial and post colonial Oyo State, the author adopted a multi data source approach principally to provide supplementary information. A historical geographical approach is adopted in the discussion on the relationship between the colonial and post colonial economic and spatial structures and the development and diffusion of tailoring industry. Also, in tracing the impact of these colonial structures on the tailoring development, emphasis is placed on a descriptive approach. To test the hypotheses on the relationship between the spatial diffusion of informal tailoring industry and urban hierarchy in Oyo State, a probability of location model is designed and used. Based on the probability of location index, the actual and the expected patterns of diffusion and development, in time and space, of the informal tailoring industry, are compared. The relevance of the variables included in the construction of the probability of location model is tested, using Spearman's Rank-Order Correlation method. (Abstract shortened by UMI.)
Keywords: History, African.